2020
DOI: 10.46827/ejes.v7i9.3267
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship Between Psychological Well-Being, Self Esteem, Perceived General Self-Efficacy, Level of Hope and Cognitive Emotion Regulation Strategies

Abstract: <p>In this study, the relationship between pre-service teachers' psychological well-being levels and self-esteem, perceived general self-efficacy, cognitive emotion regulation strategies and hope variables were investigated together with how these variables predicted pre-service teachers' psychological well-being. The research was conducted via relational screening model. The research group consists of a total of 403 participants including 206 females and 197 males, who received pedagogical formation edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…The coping resources for individuals with low self-esteem are limited to support their mental health (Taylor and Stanton, 2007). Self-esteem has been an important predictor factor of an individual's psychological well-being (Akfirat, 2020;Chen et al, 2013;Disabato et al, 2016). Past studies have found that self-esteem has a significant relationship with psychological well-being among communities of different life backgrounds, such as university students, caregivers in welfare homes, and converts (Akfirat, 2020;Asli Azad et al, 2018;Yasin et al, 2018).…”
Section: Self-esteem and Psychological Well-beingmentioning
confidence: 99%
“…The coping resources for individuals with low self-esteem are limited to support their mental health (Taylor and Stanton, 2007). Self-esteem has been an important predictor factor of an individual's psychological well-being (Akfirat, 2020;Chen et al, 2013;Disabato et al, 2016). Past studies have found that self-esteem has a significant relationship with psychological well-being among communities of different life backgrounds, such as university students, caregivers in welfare homes, and converts (Akfirat, 2020;Asli Azad et al, 2018;Yasin et al, 2018).…”
Section: Self-esteem and Psychological Well-beingmentioning
confidence: 99%
“…With the development of a constructive psychological perspective, research patterns linked to people's well-being gained traction (Akfirat, 2020). In today's culture, a lack of well-being is a pervasive and difficult task (Zuo et al, 2017).…”
Section: Literature Review Psychological Well-beingmentioning
confidence: 99%
“…Thus, this article is an attempt to fill the gap of the concept of emotion regulation strategies to understand, identify and characterize it among teachers. Scholars are attracted on how teachers regulate their emotions and examined it from various perspectives (Brouskeli et al, 2018;Conde, 2018;Lamminpaa & Vesterinen, 2018), (Borrachero et al, 2019), (Akfirat, 2020;Jeans, 2020;Uzuntiryaki-Kondakci et al, 2020;Wei et al, 2021), and (Han & Xu, 2021;Keleynikov et al, 2022;Uzuntiryaki-Kondakci et al, 2021). Although there are many studies on teachers on how they regulate their emotions, but there was still an insufficient review by scholars systematically regarding existing studies.…”
Section: Research Gap-the Existing Studies Related To Emotion Regulat...mentioning
confidence: 99%
“…The teachers also are aware of their own competence by just overcoming it (Borrachero et al, 2019). It is hypothesized that the association between self-efficacy and positive emotion is found and it may done by implementing self-regulated learning skills (Conde, 2018), together with other variables namely self-esteem, adaptive and maladaptive cognitive emotion regulation techniques, and hopelessness were the predictor of psychological well-being (individually and together) (Akfirat, 2020).…”
Section: The Themes and The Sub-themes Emotionmentioning
confidence: 99%